Implementation of Deradicalization In the Framework of Handling Criminal Acts of Terrorism in the Legal Area of the Central Sulawesi Regional Police - Robi Utomo; Sulbadana; Jubair; Awaluddin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to examine the implementation of deradicalization in the context of handling criminal acts of theism in the jurisdiction of the Central Sulawesi Police. The implementation of deradicalization in the jurisdiction of the Central Sulawesi Police is carried out by several parties, namely: Densus, and Ops Madago Raya. Each of these parties in carrying out their activities is not integrated, but coordinates with each other. Activities carried out by Densus are approaching former terrorism prisoners and families, with the aim of repairing and regaining trust, then synergizing with various institutions and district governments, carrying out supervision of former terrorism prisoners who receive assistance, separating former terrorism prisoners and families from radical groups, and mobilizing religious leaders, community leaders, and the community to build resilience so as not to be influenced by radicalism. The research method used is empirical legal research with a qualitative approach. Data collection techniques through observation, interviews and documentation. The location of this research is in 4 districts which are Madago Raya operation areas, namely Sigi-Biromaru Regency, Parigi-Moutong Regency, Poso Regency, and Tojo Una-Una Regency, Central Sulawesi Province. The results of the research are in the implementation of deradicalization in the jurisdiction of Central Sulawesi Police, the stages carried out by Idensos, Ops Madago Raya, and LPMS refer to Law No. 5 of 2018 through the stages of identification and assessment, rehabilitation, social re-integration and economic independence with various positive, persuasive and humanist activities.